Photoreductive synthesis of monodispersed Au nanoparticles with citric acid as reductant and surface stabilizing reagent. Issue 11 (18th January 2017) - Shiraishi, Yasuhiro; Tanaka, Haruki; Sakamoto, Hirokatsu; Ichikawa, Satoshi; Hirai, Takayuki
Abstract : UV irradiation of water containing HAuCl4 and citric acid at room temperature successfully produces monodispersed Au nanoparticles. The size of Au particles is easily tuned by the intensity of UV light and the amount of citric acid. Abstract : Colloidal suspensions of gold nanoparticles (AuNPs) in water can be prepared by heating water containing HAuCl4 with citric acid as reductant and surface stabilizing reagent. This thermal reduction method, however, promotes aggregation of the formed AuNPs, resulting in bimodal distribution of AuNPs. Here we report that UV (254 nm) irradiation of water containing HAuCl4 with citric acid at room temperature successfully reduces HAuCl4 and produces monodispersed AuNPs, while suppressing aggregation of the formed AuNPs. Changing the intensity of UV light or the amount of citric acid added successfully produces AuNPs with tunable sizes and narrow size distributions.